Primary Bedaquiline Resistance Among Cases of Drug-Resistant Tuberculosis in Taiwan - Wu, Sheng-Han; Chan, Hsin-Hua; Hsiao, Hseuh-Chien; Jou, Ruwen (Frontiers in Microbiology, 2021)
Bedaquiline (BDQ), which is recommended for the treatment of drug-resistant tuberculosis (DR-TB), was introduced in Taiwan in 2014. Due to the alarming emergence of BDQ resistance, we conducted BDQ resistance analyses to strengthen our DR-TB management program. This retrospective population-based study included initial Mycobacterium tuberculosis isolates from 898 rifampicin-resistant (RR) or multidrug-resistant (MDR) TB cases never exposed to BDQ during 2008–2019. We randomly selected 65 isolates and identified 28 isolates with BDQ MIC<0.25 µg/mL and MIC≥0.25 µg/mL as the control and study groups, respectively. BDQ phenotypic drug susceptibility testing (DST) using the MGIT960 system and Sanger sequencing of the atpE, Rv0678 and pepQ genes were conducted. Notably, 18 isolates with BDQ MIC=0.25 μg/mL, 38.9% (7/18) and 61.1% (11/18) isolates were MGIT-BDQ resistant and susceptible, respectively. Consequently, we recommended redefining MIC=0.25 μg/mL as an intermediate-susceptible category to resolve discordance between different DST methods. Of the 93 isolates, 22 isolates were MGIT-BDQ-resistant and 77.3% (17/22) of MGIT-BDQ-resistant isolates harbored Rv0678 mutations. After excluding 2 MGIT-BDQ-resistant isolates with borderline resistance (GU400growth control-GU100BDQ≤1 day), 100% (15/15) harbored Rv0678 gene mutations, including 6 novel mutations [g-14a, Ile80Ser (N=2), Phe100Tyr, Ala102Val, Ins g 181–182 frameshift mutation (N=2), and Del 11–63 frameshift mutation, and whole gene deletion (N=2)]. Since the other 22.7% (5/22) MGIT-BDQ-resistant isolates with borderline resistance (GU400growth control-GU100BDQ≤1 day) had no mutation in three analyzed genes. For isolates with phenotypic MGIT-BDQ borderline resistance, checking for GU differences or conducting genotypic analyses are suggested for ruling out BDQ resistance. In addition, we observed favorable outcomes among patients with BDQ-resistant isolates who received BDQ-containing regimens regardless of Rv0678 mutations. We concluded that based on MIC≥0.25 µg/mL, 3.1% (28/898) of drug-resistant TB cases without BDQ exposure showed BDQ resistance, Rv0678 was not a robust marker of BDQ resistance, and its mutations were not associated with treatment outcomes.